Multicolor emission based on a N, N′—Disubstituted dihydrodibenzo [a, c] phenazine crown ether macrocycle - Ma, Chang-Shun; Yu, Chengyuan; Zhao, Cai-Xin; Zhou, Shang-Wu; Gu, Ruirui (Frontiers in Chemistry, 2022)
Dynamic fluorophore 9,14-diphenyl-9,14-dihydrodibenzo[a,c]phenazine (DPAC) affords a new platform to produce diverse emission outputs. In this paper, a novel DPAC-containing crown ether macrocycle D-6 is synthesized and characterized. Host-guest interactions of D-6 with different ammonium guests produced a variety of fluorescence with hypsochromic shifts up to 130 nm, which are found to be affected by choice of solvent or guest and host/guest stoichiometry. Formation of supramolecular complexes were confirmed by UV-vis titration, 1H NMR and HRMS spectroscopy.